Case Report: Behavioral Disorder Following Hemispherotomy: A Valproate Effect? - Makridis, Konstantin L.; Triller, Sebastian; Atalay, Deniz A.; Prager, Christine; Elger, Christian E.; Kaindl, Angela M. (Frontiers in Neurology, 2021)
Abstract Background: Hemispherotomy is an epilepsy surgery procedure applied to cure particularly pharmacorefractory lesional epilepsy due to unihemispheric pathologies. Such a disconnection of an entire hemisphere is followed by reorganizational processes. Methods: We describe an acute aggravation of behavioral problems following a hemispherotomy in a patient treated with valproic acid, which subsided once valproate was discontinued. Results: A nine-year-old boy with drug-resistant epilepsy caused by the residua of a perinatal stroke treated for several years with valproic acid and lamotrigine underwent hemispherotomy. Shortly after surgery, minimal pre-operative behavioral problems intensified dramatically and aggression occurred as a new symptom. Assuming a correlation between valproate treatment and the postoperative altered neuronal network, we tapered off valproate. Behavioral problems decreased in intensity with the reduction of valproate dose and disappeared after drug discontinuation. Conclusion: We describe severe behavioral problems after hemispherotomy that subsided with tapering off valproate. While we cannot rule out a spontaneous correction of a post-hemispherotomy network dysregulation, our report raises awareness to possible altered effects of the anticonvulsant valproic acid parallel to reorganizational processes after hemispherotomy. Key words: drug resistant epilepsy, pediatrics, behavioral problems, valproate, epilepsy surgery